EFFECT OF THE ADDITION OF STYRENE–BUTADIENE RUBBER LATEX ON THE WATER ABSORPTION AND COMPRESSIVE STRENGTH OF CRUMB RUBBER-MORTAR - Mohammed Fahad, Besma; Isam Mohsin, Ali (Journal of Engineering and Sustainable Development, 2016)
: In this research different mixes were prepared with Cement-Sand ratio (1:3) and Water- Cement (0.5) by weight. Four sets were prepared by partially or full replacing the sand with crumb rubber tire to fabricate the Crumb Rubber-Mortar (CRM) mixtures. The first two sets include fine crumb rubber with particles size (0.3-1 mm), The other set include coarse crumb rubber with particles size (1.18-2.36 mm).The third and fourth sets were prepared as the same first sets but with the addition of (7%) Styrene–Butadiene Rubber (SBR) latex by weight of cement. Each set was consist of different percentage of replacing the sand by crumb rubber (10,30,50,100%) by volume. Tests were conducted, including water absorption and compressive strength. Several results obtained before and after the addition of Styrene-Butadiene Rubber (SBR) which shows an increase in crumb rubber percentage cause decrease in compressive strength and water absorption; while as the density increases the compressive strength and water absorption increased before the addition of SBR. After the addition of SBR to the crumb Rubber-Mortar the compressive strength and water absorption are improved. In general fine crumb Rubber-Mortar have better properties than coarse crumb Rubber-Mortar.